2006
DOI: 10.1111/j.1538-7836.2005.01709.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low PAI‐1 activity as a risk factor for hemorrhagic diathesis

Abstract: Summary.Background: Prospective studies of the epidemiology and clinical significance of low plasminogen activator inhibitor type 1 (PAI-1) activity are lacking. Objective: To evaluate the prevalence of low PAI-1 activity in patients with a bleeding tendency in comparison with a normal population. Methods: In 586 consecutive patients, referred because of bleeding symptoms, we added analyses of PAI-1 activity and tissue plasminogen activator complex with PAI-1 (t-PA-PAI-1) to the routine investigation, consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 35 publications
4
64
1
2
Order By: Relevance
“…Notably, low PAI-1 has been associated with increased bleeding tendency (15,36). As there are differences in PAI-1 activity between patients with type 1 and type 2 diabetes, we suggest that attention should be paid to the type of diabetes when performing and analyzing large clinical studies on antithrombotic drugs, especially in the era of new antithrombotic drugs where intensified prophylactic antithrombotic treatment is increasingly common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, low PAI-1 has been associated with increased bleeding tendency (15,36). As there are differences in PAI-1 activity between patients with type 1 and type 2 diabetes, we suggest that attention should be paid to the type of diabetes when performing and analyzing large clinical studies on antithrombotic drugs, especially in the era of new antithrombotic drugs where intensified prophylactic antithrombotic treatment is increasingly common.…”
Section: Discussionmentioning
confidence: 99%
“…For improvement of the precision at lower PAI-1 levels, extra measuring points were added at the lower end of the calibration curve. In addition, a point-to-point approach was used instead of linear regression as described earlier (15), with the intraassay coefficient of variation (CV) 11.5% for the low control (PAI-1 0.9 units/mL) and 5.7% for the high control (PAI-1 19.4 units/ mL) and an interassay CV 4.5% and 3.6%, respectively.…”
Section: Pai-1 Activitymentioning
confidence: 99%
“…Finally, this study was confined to patients referred for bleeding tendency. However, in healthy controls described in a previous study [11], the BMI was also significantly lower amongst 10 individuals with PAI‐1 <1 U mL −1 than amongst the 90 individuals with PAI‐1 of 1 U mL −1 or higher (21.5 vs. 23.7; P = 0.04 in two‐tailed Mann–Whitney test). We did not have samples available to test the mediators of inflammation and components of the metabolic system.…”
Section: Discussionmentioning
confidence: 56%
“…The characteristics of the patients are described in Table 1. The concentration of tPA‐PAI‐1 antigen ranged between 0.02 and 16.9 ng mL −1 and none of them had a null mutation [11]. In the univariable analysis, patients with low PAI‐1 activity were significantly younger and had a lower BMI, and a higher proportion of the females used oral oestrogens.…”
Section: Resultsmentioning
confidence: 99%
“…25 However, the prevalence of the genetic polymorphisms associated with PAI-1 have been shown to be similar for individuals with low PAI-1 activity and a bleeding tendency and healthy controls with significantly higher PAI-1 activity. 33 Nevertheless, our lack of polymorphism data are an acknowledged limitation of this study that future studies should address. Because it has been demonstrated that the ratio of PAI-1 activity to antigen concentrations can differ in people with type 2 diabetes compared with nondiabetic individuals, 34 future studies of the relationship between PAI-1 and diabetes complications should measure both PAI-1 activity and antigen concentrations.…”
Section: Discussionmentioning
confidence: 99%